Fatores associados à alteração da qualidade de vida em pacientes com esquizofrenia em uso de antipsicóticos atípicos. - Álex Brunno do Nascimento Martins (2023)
Schizophrenia is a mental disorder that affects the perception and thinking of individuals. It is known that the disease involves not only life expectancy, but also the health-related quality of life (HRQoL) of the affected individuals. Studies have investigated the relationship between QVRS and schizophrenia, but few validate the dynamics of the variations in QVRS over time. This work aims to evaluate the factors related to HRQoL alteration in patients with schizophrenia using atypical antipsychotics in the Unified Health System (SUS). The work, an open prospective cohort that accompanies 152 patients for 12 months, is an integral part of the SCHEEA project (Schizophrenia Economics and Effectiveness Assessment). Were collected data on HRQoL, psychological symptoms, social functioning and other relevant aspects. By means of a linear regression model, the HRQoL, in the form of utility, was classified as variable dependent and other information collected were classified as variable independent. Identified that problems or instability in areas such as mobility, personal care, habitual activities, sleep, discomfort, anxiety and depression are associated with a lower QVRS. It is suggested that early identification and treatment of physical and psychological symptoms, in addition to promoting autonomy and functionality, are essential to improve the HRQoL of patients with schizophrenia in SUS. This study contributes to the management of population care, highlighting the importance of multidimensional approaches that consider various aspects of care.